Preparing Interns to Use Functional Story-Based Instruction to Teach Students With a Severe Intellectual Disability in Rural Schools. (December 2019) - Hyer, Glenda; Cooper-Duffy, Karena
The primary purpose of this study was to prepare special education interns to implement two-task analyses to teach elementary students with severe intellectual disability (SID) emergent literacy and hand washing skills. The secondary purpose was to evaluate the effect of intern instruction on both the independent emergent literacy and hand washing responses of the students. A multiple probe across participant design was used to evaluate the effects of a multicomponent instruction package on the number of steps interns completed correctly on story-based and hand washing task analyses. A second simultaneous multiple probe across students design was used to evaluate the effects of functional story-based instruction on the independent emergent literacy and hand washing responses. Collateral behaviors showed as interns correctly implemented the steps of the story-based and hand washing task analyses, the students with SID increased emergent literacy and hand washing responses. Implications for rural educators are provided.